If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(7x-2)+3(16-5x)-4(3x+5)=-19
We simplify the equation to the form, which is simple to understand
4(7x-2)+3(16-5x)-4(3x+5)=-19
Reorder the terms in parentheses
+(+28x-8)+3*(16-5x)-4*(3x+5)=-19
Remove unnecessary parentheses
+28x-8+3+*(+16-5x+)-4+*(+3x+5+)=-19
Reorder the terms in parentheses
+28x-8+(+48-15x)-4*(3x+5)=-19
Remove unnecessary parentheses
+28x-8+48-15x-4+*(+3x+5+)=-19
Reorder the terms in parentheses
+28x-8+48-15x+(-12x-20)=-19
Remove unnecessary parentheses
+28x-8+48-15x-12x-20=-19
We move all terms containing x to the left and all other terms to the right.
+28x-15x-12x=-19+8-48+20
We simplify left and right side of the equation.
+1x=-39
We divide both sides of the equation by 1 to get x.
x=-39
| 5x-3=8x+9 | | -6+2x-5=5x+10-3 | | -4b(4b+4)+(17b-5)=0 | | a^2+11a-42=0 | | v^2-2v-32=-8 | | y+3x-6=-8x+6x^2 | | 2X-11= | | x+2x+1=97 | | b^2+11b+26=-4 | | (4x^2-2)(4x-8)-(5x-2)(3x^2+8)=0 | | -7x+9=11x-27 | | -7x+9=11x-7 | | n^2+4n=12 | | 6-3x=4-2x | | x^2-4n-12=0 | | 7x^2=35x | | m^2+6m-7=0 | | -16+x=x+11 | | 14h+4-9h-1=h+7-2h+2 | | N^2-4n-12=0 | | -x^2+2400x-1320000=80000 | | 3d+18=21 | | -x^2+2400x-1320000=0 | | 64=-16t^2+64t+4 | | 4x+2(24-4x)=24 | | 2b-15=33 | | 10k+5=65 | | 6=3k+21 | | 1=4+2b+1-1-b | | 8=4n-3 | | 1=4+2b+1-a-b | | 1=4+2b+1-1-a-b |